Enhancing Wall Magazine Management Effectiveness at Patih Selera Elementary School - Muhammad Yunus (Borneo Community Development, 2023)
The wall magazine in an educational environment serves as a crucial tool in facilitating communication, disseminating information, and encouraging participation within the realm of learning. This community engagement project aims to introduce and implement wall magazine management concepts at Patih Selera Elementary School (SDN), with the goal of enhancing efficiency and effectiveness in information dissemination to students, teachers, parents, and the school community. The project methodology comprises several stages, including identifying needs and challenges in wall magazine management, developing management guidelines, conducting training for teachers and students regarding their contributions to content creation, as well as implementing and evaluating the outcomes. Developing students' skills in writing, designing, and managing magazine content is a primary focus of this initiative. Results of this engagement showcase significant improvements in collaborative efforts among teachers, students, and parents in gathering information, designing layouts, and distributing the wall magazine. Student involvement in the creative process and increased parental contributions in terms of feedback and support have collectively led to a more informative and relevant wall magazine. Additionally, structured and organized management optimizes production and distribution processes, expediting information dissemination. This engagement article sheds light on the implementation of wall magazine management within the elementary education context. The positive outcomes derived from this initiative contribute to fostering an environment of informed, engaged, and collaborative learning. The experiences shared in this project can potentially serve as a reference for other schools, aiding them in developing effective and sustainable wall magazine management practices